2020
DOI: 10.1111/jcpe.13266
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of aggressive periodontitis: A systematic review and meta‐analysis

Abstract: Aim The prevalence of aggressive periodontitis (AgP) varies considerably between studies. The aim of this meta‐analysis was to estimate, throughout the world, the prevalence of this disease. Materials and Methods Pubmed/Medline, Scopus, Science Direct, EBSCO and Cochrane library were systematically searched up to March 2018. Study selection criteria included cross‐sectional studies reporting prevalence of AgP in non‐specific population and permanent dentition. We assessed risk of bias using the Joanna Briggs I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 64 publications
2
28
1
Order By: Relevance
“…As indicated above, we focused on a specific type of periodontitis formerly recognized as AgP because this disease form has been studied for a long time 6,21 and is highly prevalent in young Moroccan individuals 2‐4,6 . The 2017 World Workshop on the Classification of Periodontal and Peri‐Implant Diseases and Conditions introduced a new periodontitis classification scheme 22 in which chronic periodontitis (CP) and AgP are now grouped under a single category, periodontitis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As indicated above, we focused on a specific type of periodontitis formerly recognized as AgP because this disease form has been studied for a long time 6,21 and is highly prevalent in young Moroccan individuals 2‐4,6 . The 2017 World Workshop on the Classification of Periodontal and Peri‐Implant Diseases and Conditions introduced a new periodontitis classification scheme 22 in which chronic periodontitis (CP) and AgP are now grouped under a single category, periodontitis.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated a geographic variation in the prevalence of periodontitis in children and young adults, with a high prevalence in Africa and in populations of African descent 1‐6 . An epidemiologic study conducted in Morocco, North Africa, 4 reported that periodontitis affected 4.9% of individuals aged 12‐25 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of aggressive periodontitis varies significantly between populations and different racial/ethnic origins (Susin et al, 2014). The pool prevalence of aggressive periodontitis was 1.6% and relatively higher prevalence was found in Africa (4.2%) (Bouziane et al, 2020). In a small population study in Malaysia, the prevalence of aggressive periodontitis was 5.3% (Yee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Destruction of the periodontal tissue begins in the area of the first molars and incisors, and with aging it can involve the periodontium of adjacent teeth. It affects the peridontal tissue of at least three permanent teeth, except the first molars and incisors [1].…”
Section: Introductionmentioning
confidence: 99%